Interconnectedness of financial conglomerates - Gaël Hauton; Jean-Cyprien Héam (Risks, 2015)
Being active in both the insurance sector and the banking sector, financial conglomerates intrinsically increase the interconnections between the banking sector and the insurance sector. We address two main concerns about financial conglomerates using a unique database on bilateral exposures between 21 French financial institutions. First, we investigate to what extent to which the insurers that are part of financial conglomerates differ from pure insurers. Second, we show that in the presence of sovereign risk, the components of a financial conglomerate are better off than if they were distinct entities. Our empirical findings bring a new perspective to the previous results of the literature based on using different types of data.
Keywords: G22; G28; 330; interconnectedness; financial conglomerate; contagion; systemic risk